Echoes of the Thai Accent: Examining Its Impact on English Learning and Teaching Strategies - Aisyah, Aisyah; Erizar, Erizar; Husna, Faizatul; Oserio, Abigael Mallari (Universitas Teuku Umar, 2025)
This study examines the challenges faced by English teachers in Thailand when teaching students with a Thai accent and explores the strategies they employ to address these difficulties. The phonetic differences between Thai and English often lead to pronunciation difficulties, comprehension issues, and reduced self-confidence among students. Using qualitative methods, this research gathered data from interviews with three English teachers at Tessaban 2 Bansadao School. The findings indicate that limited English exposure, difficulty distinguishing certain phonemes, and the influence of Thai tonal and intonation patterns significantly hinder students’ learning. In response, teachers implemented phonetic drills, multimedia-assisted instruction, and various communication techniques to enhance pronunciation and engagement. Rather than focusing on accent reduction, the study emphasizes the importance of intelligibility in spoken English. By identifying accent-specific teaching strategies, this research contributes to more effective instructional practices for Thai-accented learners of English, ultimately improving their pronunciation and overall language skills.